An Overview of the Building Energy Management System Considering the Demand Response Programs, Smart Strategies and Smart Grid - Shakeri M. (MDPI AG, 2023)
Electric power transmission networks; Energy efficiency; Energy management; Smart power grids; Virtual storage; Building energy management systems; Demand response programs; Efficiency and performance; Electricity demands; Home energy management systems; Load management techniques; Management systems; Technical information; Energy management systems